Test automation tools: A comparison between Selenium, Jenkins and Codeception - Stouky, Ali; Jaoujane, Btissam; Daoudi, Rachid; Chaoui, Habiba (International Journal of Engineering and Technology, 2018)
Software development life cycle consists of many phases and software testing is one of them. Itâ€™s a very important one and ensures the quality of the software by fixing bugs which can be done with automated testing to reduce human intervention and to save time and effort consumed in the manual testing. The entire process of testing can be automated to reduce time and cost easily with the help of automated testing tools. Thus, it is crucial to select the suitable tool that meet the needs of the software system. This paper provides a feasibility study for the most commonly used web testing tools to determine their usability and effectiveness.Â